Pig liver esterase (PLE) extraction. - Trevisan, Henrique Celso; Medeiros, Joao Batista de; Favero Lisboa, Helen Cristina (Soc Brasileira Quimica, 2006)
A simple, fast and low-cost methodology was optimized, seeking preparation of a crude pig liver esterase (PLE) concentrate. Basically, the method consisted of the following steps: liver homogenization, acetone washing, enzyme extraction and purification/concentration. Starting from 1 kg of fresh liver more than 200 W of PLE suspension were obtained after 8 hours, at an estimated cost of US$0.21/kU. The PLE concentrate thus obtained was stable, showing 96-100% of the initial activity after 7 months in refrigerator at 4 degrees C.
Keywords: porcine liver esterase; PLE; biocatalysis